Hard X-ray phase-contrast tomography of non-homogeneous specimens: Grating interferometry versus propagation-based imaging - Ruiz-Yaniz, Maite; Zanette, Irene; Sarapata, Adrian; Birnbacher, Lorenz; Marschner, Mathias; Chabior, Michael; Olbinado, Margie; Pfeiffer, Franz; Rack, Alexander (Journal of Synchrotron Radiation, 2016)
X-ray phase-contrast imaging is an effective approach to drastically increase the contrast and sensitivity of microtomographic techniques. Numerous approaches to depict the real part of the complex-valued refractive index of a specimen are nowadays available. A comparative study using experimental data from grating-based interferometry and propagation-based phase contrast combined with single-distance phase retrieval applied to a non-homogeneous sample is presented (acquired at beamline ID19-ESRF). It is shown that grating-based interferometry can handle density gradients in a superior manner. The study underlines the complementarity of the two techniques for practical applications.
CRIS-Team Scopus Importer:2023-03-08
Keywords: phase contrast; phase retrieval; X-ray imaging; X-ray microtomography